1887 N.M. Laws 56, § 3 - (:unkn) unknown (My University, 1887)
Ch. 30, § 3: Any person who shall unlawfully assault or strike at another with a deadly weapon, upon conviction thereof shall be punished by a fine not exceeding one thousand dollars, or by imprisonment at hard labor in the county jail or territorial penitentiary, not exceeding three years, in the discretion of the court or jury trying the same.
Keywords: COMMITTING CRIME W/ WEAPON